Fine structure of the Isovector Giant Dipole Resonance: a survey with the (p,p') reaction at zero degrees - Jingo, Maxwell (My University, 2014)
This investigation involves a survey of the fine structure phenomenon of the Isovector Giant Dipole Resonance (IVGDR) over a wide mass range of nuclei, from 27Al, 40Ca, 56Fe, 58Ni to 208Pb, using inelastic proton scattering at 200 MeV. Proton detection is accomplished using the recently commissioned zero-degree facility of the K600 magnetic spectrometer at iThemba LABS. Inelastic proton experiments at zero degrees are very selective to excitations with low angular momentum transfer, and therefore ideal for studies of the IVGDR. This is because such experiments simplify the analysis of the many contributions to the spectra due to the complex nature of the nuclear interaction. The ability to make precise measurements of the properties of the IVGDR demonstrated by this work opens up new challenges to both experimental and theoretical work in nuclear structure. This is a survey of the (p,p′) reaction at zero degrees as a probe to study properties of the GDR and also the low energy E1 strength with high energy-resolution. Such a data base will provide more stringent tests of nuclear theory and the progress is seen in the details obtained. These tests can only be described by microscopic models including complex degrees-of-freedom. This should lead to new insights into the underlying interactions responsible for the nature of the electric dipole strength in nuclei. In the present study, double-differential cross-sections were converted to equivalent photo-absorption cross-sections and their results compared to previously published photo-absorption data. An excellent correspondence in the excitation-energy region of the Giant Dipole Resonance (GDR) was noticed between the two data sets. The fine structure observed can be described using characteristic energy scales, arising mainly from Landau damping (even though the spreading width may also play a role). The extraction of these characteristic energy scales which are a signature for the decay process was achieved through the use of wavelet analysis. Furthermore, thanks to the recent advances in computational power and techniques, microscopic shell model-based calculations lead to new insights into the underlying properties of the nuclear interaction which are responsible for the collective behaviour evidenced by the existence and properties of the IVGDR. In addition to the extraction of characteristic energy scales, this study also provides level densities of J = 1− states. In order to extract nuclear level densities, there is need to eliminate instrumental background and other contributions to the spectra from (p,p′) scattering using the model-independent Discrete Wavelet Transform (DWT) method. Level densities of J = 1− states are determined using the fluctuation analysis technique and comparisons are made with the phenomenological Back Shifted Fermi Gas (BSFG) model predictions, calculations of the Hartree Fock- Bogoluibov (HFB) microscopic model and Hartree Fock-Bardeen-Cooper-Schrieffer (HF-BCS) predictions. Finally, this survey will simultaneously provide bench-marks on the capabilities and limitations of the new zero-degree facility important for planning of the future experimental work.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2014.
Keywords: Nuclear structure.; Nuclear reactions.